The Accident Compensation Scheme: A Case Study in Public Policy Failure - Wilkinson, Bryce (Victoria University of Wellington Law Review, 2003)
Among groups challenging ACC policy during this decade, the New Zealand Business Roundtable offered the most passionate critique of the scheme and its founding assumptions. The New Zealand Business Roundtable argued that the public interest was better served by promoting consumer choice in insurance coverage, delivered in a competitive market by private insurers. This article explains the origins and rationale for this market-based critique, and provides a spirited statement of an economic philosophy that proved influential in shaping legislative reforms in the 1990s.